Cheeky Witnessing. Issue 1 (March 2020) - Fletcher, Ruth
Feminists witness legal worlds as they observe, document and share nothing less than the reproduction of life itself. The world of the abortion trail, where people and things move across borders to change life's reproduction, has generated a rich variety of legal sources, figures and objects for feminist witnessing. In watching how feminist activists improvise with sources, figures and objects of legal consciousness on the abortion trail, this article seeks to contribute to critical understanding of a plurality of witnessing practice, particularly as it emerges in diaspora space. Focusing on Murphy's concept of immodest witnessing, with its attention to bodies, protocols and apparatuses as constituents of knowledge, the article thinks with the diasporic feminist performance group, Speaking of I.M.E.L.D.A., about how they used self-examination, collaboration and knowledge-sharing on the trail to repeal Ireland's 8 th Amendment. The article argues that their improvisation with legal consciousness of reproductive choice enacts 'cheeky witnessing'. Cheeky witnessing has three dynamics as a method of observation. First, it is messy and irreverent in innovating with names to display the mixed genealogies of feminist knowledge. Second, cheeky witnessing generates novel subject-figures who make connections between different reproductive labourers as observers of the trail in diaspora space. Third, cheeky witnessing places funny objects, knickers in this instance, so as to join up particular public locations and make them more, if unevenly, comfortable for sexual and reproductive bodies. Cheeky witnessing shows us how committed and partial practices play a role in speaking across interests and experiences, in stretching the legal imagination and in sustaining the everyday grind of making a better world.